From inclusive laws to social practices within a society for all - Tavares, Aureliana da Silva; Rodrigues, Janine Marta Coelho (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2020)
The present article attempts to present some factors that subsidize the construction of a society for all, in which less social inequality is observed and where people with disabilities can exercise their role as citizens, moving from a segregated life to an active, social, participative life. The Brazilian Law of Inclusion or Statute of Persons with Disabilities of 2016 gave legal and constitutional apparatus to such visions, making the struggle for inclusive social actions an ideological struggle, of attitudinal actions. Inclusion of all must overcome exclusion barriers. This struggle exists and persists so that people with disabilities, those suffering from racist, religious, sexual, linguistic, cultural or social prejudices may have the same opportunities for development and social practice as those who do not.